Análisis de la autonomía privada en la transnacionalización de capitales - Cataño Berrío, Sandra Eliana (2023)
In international commercial contracts, formed by some Colombian corporations with multinational corporations, it is possible to see how relationships are built around a center - periphery model. This is done thr ough dominant and dominated institutions, and it is evidenced by the organization and operation of multinational corporations, by their relationship with national corporations, and also by the use of certain contractual terms and practices. Furthermore, a series of different elements play a part in international commercial contracts, where one can find a diverse array of sociolegal fields, among which the transnational field is dominant and most influential.